2007 46th IEEE Conference on Decision and Control 2007
DOI: 10.1109/cdc.2007.4434507
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism for energy transfer leading to conformation change in networked nonlinear systems

Abstract: Understanding mechanisms for conformation change in large networks of biological oscillators leads to comprehension of robustness notions in generic large interconnected dynamical systems. Biological systems are known to be extremely robust to most environmental perturbation while in certain situations they embrace external influence to carry out a particular task. In light of this, the connection with networked or distributed control systems becomes clear. In this paper, we study the dynamical properties of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 15 publications
4
14
0
Order By: Relevance
“…This salient feature of J suggests a directed transmission path of energy from high-frequency KMs to low ones. This is consistent with that in [84] that analyzes global dynamics occurring in nearly-integrable Hamiltonian systems. The The symbol T is the sampling period.…”
Section: Precursor Diagnostic To Coherent Swing Instabilitysupporting
confidence: 90%
“…This salient feature of J suggests a directed transmission path of energy from high-frequency KMs to low ones. This is consistent with that in [84] that analyzes global dynamics occurring in nearly-integrable Hamiltonian systems. The The symbol T is the sampling period.…”
Section: Precursor Diagnostic To Coherent Swing Instabilitysupporting
confidence: 90%
“…In particular, we point out for the loop system that incoherent bounded swings of generators lead to their coherent loss of synchronism, namely, global instability. This is motivated by [12], [13], [14] on dynamics of molecular conformation. Sec.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies, 8,9,11,24 mainly numerical, showed that this model exhibits an intriguing phenomenon of structured activations observed in many bio-molecules: While the system is robust to noise, it is sensitive to certain specific fine scale modes that can trigger the division. Figure 2 provides the numerical data for such claim.…”
Section: B Phenomenon Of Structured Activationsmentioning
confidence: 99%
“…24,38 Previous studies, 8,9,24 mainly numerical, showed that this model exhibits an intriguing phenomenon of structured activations observed in many bio-molecules: While the system is robust to noise, it is sensitive to certain specific fine scale modes that can trigger the division. Below, we will describe briefly the results of our analytical study on this intriguing phenomenon and our effort in the control of this DNA model via parametric resonance.…”
Section: Introductionmentioning
confidence: 99%